Pemikiran Ilmu Kalam dalam Menjawab Pertanyaan Kontemporer - Nadia Anggaraini; Zahrani Izzati.S; Syukri Al Fauzi Harlis Yurnalis (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
Ilmu Kalam is a branch of Islamic knowledge that focuses on theological discourse through rational and logical approaches. In the face of contemporary challenges, Ilmu Kalam must evolve to address complex modern issues that affect both individual and collective life. This article explores the relevance and contribution of Ilmu Kalam in responding to current topics such as religious pluralism, human rights, environmental crisis, modern science, and digital ethics. The thoughts of key Muslim scholars like Muhammad Arkoun, Nasr Hamid Abu Zayd, Harun Nasution, and M. Amin Abdullah are referenced to reinterpret core Islamic teachings in harmony with modern realities. This approach enables Ilmu Kalam not only to preserve essential theological principles but also to play a significant role in shaping a just, tolerant, inclusive, and sustainable society. Therefore, Ilmu Kalam should continue to be developed as a dynamic and forward-thinking discipline that bridges Islamic values with the demands and complexities of contemporary life.